Rancang Bangun Sistem Rekomendasi Jogging Track Di Kota Malang Berbasis Lokasi - Zulfikar Faras Fadila; Ratih Kartika Dewi; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Jogging is one of the cheapest sports, it doesn't even need more costs so it becomes the choice of people as a regular exercise. In the city of Malang, there are many jogging track facilities and various and adequate jogging places, some of which are not widely known by the public. There are also separate preferences and also factors when someone chooses a comfortable open space for exercise activities, namely jogging. This can cause a separate problem, for someone to choose a comfortable place according to their preferences when they wanna do jogging. The preference factors mentioned are such as track length, distance of place, and rating of the place. To solve this problem a system is needed which can recommend jogging tracks to users based on the jogging track criteria user want to find. The jogging track recommendation system was developed using the TOPSIS method. The TOPSIS method used can provide recommendations or rankings from existing alternatives sorted by priority criteria that have been determined from user preferences. The system is implemented on the Android platform because it requires user location data that can be accessed using a GPS sensor on a mobile device. From the test results, the results are 100% valid in testing for system functionality. After that, testing the algorithm validation that gets 100% results by comparing the results of the system output with manual calculations. The last is usability testing, the final score is 81.0 which can be concluded that the system tested at the end user is easy to use and quite useful for the user.